FORMULATION AND IMPLEMENTATION INFLUENCE STRATEGY OF CONTROL BUDGET SURVEY ON BUMN SUFFERING LOSSES - Eddy Mulyadi Soepardi (Jurnal Ilmiah Ekonomi Bisnis, 2009)
n general strategy establishment involved two main stages, strategy formulation and implementation. Most state-owned enterprises (BUMNs) have not had appropriate budget controlling. This unevenness reflects the disparity between real and expected condition. This phenomenon instigates the author to perform a research that focuses to discern the magnitude of the both partial and simultaneously influence of strategy formulation and strategy implementation on budget controlling. The research involves 10 BUMNs randomly chosen and to date are experiencing loss. Tested variables includestrategy formulation, strategy implementation and budget controlling. Structural Equation Modeling (SEM) built using AMOS 5 is applied in the study. Research results indicate that partially and simultaneously both strategy formulation and strategy implementation have significant positive effects on budget controlling. Strategy implementation have more dominant effect on budget controlling than strategy formulation, consecutively the determinant coefficients of both variables are 55,77% and 27,%.    Keywords: strategy formulation, strategy implementation, budget controlling